”Ett värdefullt arv till kommande generationer av estlandssvenskar”: En analys av kulturarvsprocesser kring utgåvor med visdiktaren Mats Ekmans visor - Joons Gylling, Sofia (Puls – musik- och dansetnologisk tidskrift, 2022)
This article analyses the creation and maintenance of a certain Estonia-Swedish cultural heritage: songs written in dialect by the singer-songwriter Mats Ekman (1865–1934) from Rickul/Riguldi in Estonia. The aim is to look into how Ekman’s song repertoire has been compiled, published and transmitted and what this process says about Estonia-Swedish identity. The author describes the Estonia-Swedes’ maintenance of culture within their community in exile after World War II as a multifaceted phenomenon that consisted of both memory production and culture heritage processes. Since Ekman’s songs have not been preserved in either official or NGO archives, the publications have acted both as a means of preservation and of transmitting Ekman’s repertoire. Characteristic for the transmission is that both the compilers of the publications and the primary target-groups belonged to the Estonia-Swedish community. The author suggests this kind of transmission of culture to be termed publikativt kulturarvande (publicative cultural heritageing), as the goal for the publication is to pass on cultural heritage to potential heirs and not to preserve a song-repertoire or amuse readers outside the community. Over time, an internal change took place within the target-group that went from consisting of the older generation, with their own memories of the songs, to younger generations, with none of their own memories of pre-war life in Estonia. This change affected the content of the publications as translations to standard Swedish, notes, background information and recordings of the songs were added. In the initial context, the publications with Ekman’s songs had a role of activating memory, which later evolved into a memory-creating role. During the transition between these two functions, Ekman’s songs began to be presented as Estonia-Swedish cultural heritage.